Evaluation of relationship addicton criterias with rasch model - Havaçeliği Atlam, Demet; Yüncü, Zeki; Totan, Tarık (Journal of Dependence, 2015)
Objective: In research, according to the DSM-IV diagnostic criteria proposed seven items to evaluate the addiction in partner relations within the scope of the examination of the Item Response Theory is targeted.Method: The students, studied at all faculties of Ege University, had been randomized according to faculty and class level. 1522 people were reached and 1260 people of them were evaluated in the research. IRTPRO and BILOG-MG programs has been used the analysis of research data.Results: Participants were 751 women (59.6%) and 509 male (40.4%). According to Rasch model analysis, “spending time to a relationship” of relationship addiction items was marked as Yes the most (66.5%). And then, second item of related to “withdrawal” (47.5%) followed by was observed. It was found to vary Pearson correlation coefficient between .22 and .43, Biserial item correlation coefficient between .30 and .53.Variance was found .66, standart error was found .71 related to the criterias about relationship addiction. This finding was pointed out that t value of observed differences for the criterias was found less than1.96(p
Keywords: Relationship addiction; item response theory; rasch analysis; DSM